MEMPERKUAT TRADISI BUDAYA JAWA KUNO “DJAMPI OESODO” SEBAGAI STRATEGI PENGEMBANGAN POTENSI WELLNESS TOURISM DI ERA MODERN - Shabrina Dwi Annisa; Naila Syarafina Arif; Indri Kurniawati (Bajang Institute, 2026)
Abstract: Jamu is declared as a beverage full of benefits, becoming a local treasure of Java that has been passed down by the ancestors. There is a strong philosophy that shapes the history of jamu, namely “djampi oesodo”. The philosophy of djampi oesodo emphasizes the concept of balance between nature and the human soul, body, and mind. In theory, this philosophy is in line with the concept of wellness tourism, so there is strong potential to strengthen the djampi oesodo narrative in the modern understanding of jamu, which aims to enhance the tourist experience in interpreting jamu as a healthy drink. Unfortunately, however, the djampi oesodo narrative does not go hand in hand with the popularity of modern jamu. This study uses a qualitative-descriptive method through data collection via literature review and interviews. The data in this study is used to formulate strategies to strengthen the djampi oesodo narrative as a potential wellness tourism concept in the modern era.